2021
DOI: 10.1037/pag0000576
|View full text |Cite
|
Sign up to set email alerts
|

Helping out or helping yourself? Volunteering and life satisfaction across the retirement transition.

Abstract: It has been suggested that volunteering leads to increases in well-being, particularly in older and retiring adults, and that volunteering could be used as a public health intervention to increase well-being. However, the causal relationship has been questioned. We investigated the association between voluntary work and life satisfaction in a bivariate dual-change score model, using 4 years of longitudinal data from 1,123 participants from the Health, Aging and Retirement Transitions in Sweden (HEARTS) study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 69 publications
2
35
1
Order By: Relevance
“…It is also conceivable that volunteering does not yield noteworthy effects across outcomes when actual intraindividual change is considered (cf. Bjälkebring et al, 2021). The positive associations between volunteering and SWB found in prior longitudinal research may partly represent selection effects, because cross-lagged panel models confound intraindividual change with interindividual differences (Hamaker et al, 2015;Wang & Maxwell, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is also conceivable that volunteering does not yield noteworthy effects across outcomes when actual intraindividual change is considered (cf. Bjälkebring et al, 2021). The positive associations between volunteering and SWB found in prior longitudinal research may partly represent selection effects, because cross-lagged panel models confound intraindividual change with interindividual differences (Hamaker et al, 2015;Wang & Maxwell, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the between-person associations we found-albeit small in size-suggest that more satisfied individuals self-select particularly into nonpolitical volunteering (cf. Bjälkebring et al, 2021;Hansen et al, 2018;Son & Wilson, 2012;Thoits & Hewitt, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Wit and colleagues (2015) concluded that about 75% of the well-being differences between volunteers and non-volunteers can be attributed to selection effects. Recently, researchers have increasingly addressed the within-person associations between voluntary participation and well-being and found modest effects at best (Bjälkebring et al, 2021;Dawson-Townsend, 2019;De Wit et al, 2015;Fiorillo et al, 2017;Lawton et al, 2020;Lühr et al, 2021;Meier & Stutzer, 2008). Therefore, it is important to examine within-person associations separately from between-person differences, which is possible when longitudinal data from multiple measurements are available.…”
Section: Introductionmentioning
confidence: 99%